Procurement and supply management of Eskayef Pharmaceuticals Limited - Shahnewaz, Ahmed Abid (Brac University, 2022)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2021.